Analysis of the association between APOA5 polymorphism and cholesterol lowering effects among statin users with hypercholesterolemia from HUSM, Kelantan - Tounbakjy, Mhd Houssam Iyad (2020)
Statins, HMG-CoA reductase inhibitors, have shown their efficacy in reducing one of the major risk factors for the disease i.e., the plasma cholesterol level. Patients’ responses to statin therapy have, however, been found to vary significantly. The interindividual variation can be attributed to many demographic and clinical factors including genetic factors. A single nucleotide polymorphism (SNP) in Apolipoprotein A5 (ApoA5) gene, i.e.,rs662799, was reported to result in the cholesterol-lowering effect of statins. No definitive conclusion has been drawn to date and no genetic association study among the Malaysian population has been explored on the SNP in determining statin’s cholesterol-lowering effect. Therefore, this study aims to investigate the association of ApoA5 rs662799, along with other clinical factors, on the efficacy of prescribed statins in lowering the plasma cholesterol level among hyperlipidaemic patients at the Klinik Rawatan Keluarga, Hospital Universiti Sains Malaysia, Kelantan. This is a non-interventional cross-sectional study involving 84 patients. Demographic and clinical data for patients have been collected from the hospital’s computerized database and medical folders at the Unit Record. Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) was the technique adopted for blood DNA genotyping in this study. Unprecedented damage by the pandemic COVID-19 requires an unprecedented policy change including the arrangement of this study because the genotyping method was not accomplished as planned at the beginning of the study. Nevertheless, we consider the genotype frequencies of the rs662799 SNP to have been compatible with other Asian populations i.e., Minor Allele Frequency (MAF) value of 0.29 for East Asian populations (https://asia.ensembl.org/index.html). Also, a significant difference was expected in statin’s cholesterol-lowering effects due to the rs662799 SNP, with a higher LDL-C reduction in TT-1131 genotype (the major allele) than the C-1131 allele (the minor allele) carriers. The interpretation of the expected results needs further investigation to validate the association of rs662799 SNP with respect to the effectiveness of the statin.